Evaluation of ability of dentifrices to remineralize artificial caries-like lesions - Satyawan Gangaramji Damle; Vikas Bengude; Sheeba Saini (Wolters Kluwer Medknow Publications, 2010)
Background: Human endeavors to prevent dental caries have led to the use of different modalities and agents, the most commonly used of which is fluoridated dentifrice. An in situ study was carried out to evaluate the efficacy of fluoridated dentifrices in achieving remineralization of initial caries-like lesions using surface microhardness measurements and to study the qualitative changes by scan-ning electron microscopy. Methods: Sixteen children 12-16 years of age wore a specially fabricated appliance with an artificially demineralized enamel slab for 24 hours a day, for four weeks. The children were divided into two groups, A and B. Following one week use of placebo dentifrice by both groups, group A used a fluoride dentifrice containing l000 ppm sodium monofluorophosphate, whereas group B used a placebo twice daily for 5 minutes for 21 days. Surface microhardness test carried out using a Knoop diamond indenter followed by scanning electron microscopy to evaluate the lesions. The results were statistically analyzed using the student t test. P value less than 0.05 was considered significant. Results: The average hardness recovery for the experimental group was significantly higher than that in the control group (P < 0.001). Scanning electron microscopy revealed that fluoride significantly enhances remineralization of initial caries-like lesions. Conclusion : Regular use of fluoridated dentifrices significantly enhances remineralization of white spot lesions.